The Effect of Music Therapy on the Stress Levels of Medical Students at Universitas HKBP Nommensen - Hendra; Jenny Ria Sihombing; Juliaster Marbun; Gabriella Maria Christine Sipahutar; Junita Batubara; Windos Marbun (Bulletin of Science Education, 2024)
This research explores the effect of music therapy on the stress levels of medical students at HKBP Nommensen University. With high study loads and academic pressure, medical students often experience significant stress. For this reason, this research adopts a box music therapy (BmT) approach, which combines technology and music to provide a therapeutic experience. In this study, heart rate (BPM) and galvanic skin response (GSR) sensors were used to measure participants' physiological changes before and after music therapy sessions. The measurement results showed a decrease in BPM from 120 before therapy to 100 after, and a decrease in GSR from 588 to 300, indicating a real relaxation effect. A questionnaire filled out by 28 students showed that 65% of respondents agreed that music therapy helped reduce stress, while 30% strongly agreed. Only 5% felt they were not helped, indicating a significant positive impact for the majority of participants. The music chosen in this therapy plays an important role, with song choices that support a calm atmosphere, including classical and pop music. This study confirms that music therapy is an effective strategy for stress management among medical students. Implementing this therapy in an academic environment can improve students' mental health and their quality of life while undergoing intense education. Keywords: Effect of Music Therapy, Stress Levels, Students, UHN